Pengaruh Kemampuan Kerja, Masa Kerja, dan Kompensasi Terhadap Kinerja Karyawan Bagian Marketing pada CV. XXX - Rindang Wahyuning Utami; Tri Andjarwati (Jurnal Manajemen Riset Inovasi, 2024)
This study aims to analyze the effect of Work Ability, Length of Service, and Compensation on the Performance of Marketing Department Employees on CV. XXX. The sample in this study is employees of the marketing department on CV. XXX  as many as 46 people. The sampling technique in this is saturated sampling and data collection using questionnaires. The instrument validity test uses Pearson Correlation, while the reliability test uses Cronbach alpha, and data analysis is carried out using multiple linear regression analysis techniques. The results of this study found that: (1) Work Ability has a positive and significant effect on the performance of marketing employees on CV. XXX. (2) Employment has a positive and significant effect on the performance of marketing employees on CV. XXX. (3) Compensation has a positive and significant effect on the performance of marketing employees on CV. XXX. (4) Work Ability, Length of Service, and Compensation have a positive and significant effect on the performance of marketing employees on CV. XXX.